2020
DOI: 10.1200/go.20.00209
|View full text |Cite
|
Sign up to set email alerts
|

Scientia Potentia Est: How the Italian World of Oncology Changes in the COVID-19 Pandemic

Abstract: PURPOSE After coronavirus disease 2019 (COVID-19) was declared a pandemic by the WHO, a response from the Italian Health System to react to an unprecedented condition became necessary and sudden. The COVID-19 pandemic has required oncologists to redefine clinical organization and patient management. The purpose of our study was to document the difficulties emerging during the SARS-CoV-2 pandemic in Italian oncology. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…This assumption had a great impact on scheduled treatment and on clinical reorganization and induced anxiety and fears in patients, as well as in oncology healthcare professionals. 7 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…This assumption had a great impact on scheduled treatment and on clinical reorganization and induced anxiety and fears in patients, as well as in oncology healthcare professionals. 7 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 disease outbreak between late 2019 and 2020 has dramatically changed people's everyday life. All countries around the world are engaged in a massive struggle in order to slow down the pandemic and protect the population, in particular the frailest groups [14]. Patients and healthcare workers have been negatively impacted by the ongoing pandemic, not only physically but mentally too [15].…”
Section: Discussionmentioning
confidence: 99%
“…A model using the current pandemic context predicts that cancer-related cases and deaths attributed to COVID-19 will be a significant burden on health systems in Latin America, 45 but studies using empirical data are lacking in this space. One study tackled cancer care in the era of COVID-19: A survey of oncology health professionals in Italy indicated that 93% of their departments had reorganized routine clinical activity due to COVID-19, but only 41% felt adequately trained about the new COVID-19 required procedures 46 (#621, Type V). The heterogeneity of responses and the lack of evidence regarding responses in LMICs need to be further investigated.…”
Section: Malariamentioning
confidence: 99%